Analisis Banjir Genangan di Kawasan Tembalang dan Sekitarnya - Sidiq, Wahid Akhsin Budi Nur; Hanafi, Fahrudin; Priakusuma, Dwi; Haruman, Willar; Sumarso, Muhammad Yunan; Setyowati, Nanik (Badan Riset dan Inovasi Daerah Kota Semarang, 2022)
Semarang City has a low and flat topography in several areas so that it has a high risk of inundation during the rainy season with a spatial distribution in the city center area. In 2022 inundation floods have inundated 877.66 hectares, one of which is in the Tembalang area and its surroundings with a height of around 275 MDPL which occurred in 20 locations with an area of around 33.62 hectares, where the area is the downstream part of the Babon Watershed. The results of the analysis of rain in the Babon watershed area for 20 years show that it is relatively stable, not too much variation, where the results of calculating the rational flood discharge for 2022 with a return period of 2 years are around 25.80 m³/s. Furthermore, the morphometric analysis of the watershed shows that the shape of the Babon watershed is relatively elongated with a circularity ratio <0.50, the density index of the river is 0.25 – 10 km/km² which is in the medium density category with a relatively long Time Concentration (TC) of around 3.2 hours so that it is less thus impacting flooding downstream. The Babon watershed runoff coefficient is affected by land cover conditions, where the interpretation results show that there was a change in land cover from 2002 – 2022 for the area of built-up land which increased by 708.44 hectares and the vegetation area decreased by 486.77 hectares. Analysis of channel capacity shows that there is potential for overflow from existing channels in 7 sub-watersheds which will result in inundation. The conclusion of this study shows that rainfall over the past 20 years has been relatively stable and the morphometry of the watershed has not had much impact on downstream flooding, the main river capacity of the Babon DAS is still sufficient to accommodate the planned flood discharge with a return period of 25 years. So that inundation that occurs is more caused by changes in land cover and drainage capacity in the downstream.